"Social policy and intelligence" Redux: a tribute to Edward Zigler. (May 2021) - Sternberg, Robert J.
Abstract: I present a theory of adaptive intelligence and discuss why I believe adaptive intelligence, rather than general intelligence, is the kind of intelligence upon which we should focus in today's world. Adaptive intelligence is the ability to adapt to, shape, and select real-world environments in ways that result in positive outcomes not only for oneself, but also for others and the world. Edward Zigler was among the first to recognize the importance of levels of adaptation to intellectual deficiency, arguing from early on that intellectual challenges needed to be recognized not just in terms of IQ but also in terms of adaptive functioning. Adaptive intelligence is compared to and contrasted with general intelligence, which is usually defined as the first factor in a factor analysis of psychometric tests. I first introduce the main issues in the article. Then I discuss how one even would decide what intelligence is. Next I discuss broader theories of intelligence and especially the theory of adaptive intelligence. Then I talk about the perishability of theories of intelligence and other things—to what extent are they set up so that people are willing and able to move beyond them? Finally, I discuss how individual outcomes do not necessarily predict collective outcomes.